An NADPH Oxidase RBOH Functions in Rice Roots during Lysigenous Aerenchyma Formation under Oxygen-Deficient Conditions. Issue 4 (28th March 2017) - Yamauchi, Takaki; Yoshioka, Miki; Fukazawa, Aya; Mori, Hitoshi; Nishizawa, Naoko K.; Tsutsumi, Nobuhiro; Yoshioka, Hirofumi; Nakazono, Mikio
Abstract : Production of reactive oxygen species by the NADPH oxidase RBOHH, which is activated through calcium-dependent protein kinases, is essential for lysigenous aerenchyma formation in rice roots. Abstract: Reactive oxygen species (ROS ) produced by the NADPH oxidase, respiratory burst oxidase homolog (RBOH), trigger signal transduction in diverse biological processes in plants. However, the functions of RBOH homologs in rice ( Oryza sativa ) and other gramineous plants are poorly understood. Ethylene induces the formation of lysigenous aerenchyma, which consists of internal gas spaces created by programmed cell death of cortical cells, in roots of gramineous plants under oxygen-deficient conditions. Here, we report that, in rice, one RBOH isoform (RBOHH) has a role in ethylene-induced aerenchyma formation in roots. Induction of RBOHH expression under oxygen-deficient conditions was greater in cortical cells than in cells of other root tissues. In addition, genes encoding group I calcium-dependent protein kinases (CDPK5 and CDPK13) were strongly expressed in root cortical cells. Coexpression of RBOHH with CDPK5 or CDPK13 induced ROS production in Nicotiana benthamiana leaves. Inhibitors of RBOH activity or cytosolic calcium influx suppressed ethylene-induced aerenchyma formation. Moreover, knockout of RBOHH by CRISPR/Cas9 reduced ROS accumulation and inducible aerenchyma formation in rice roots. These results suggest that RBOHH-mediated ROS production, which is stimulated by CDPK5 and/or CDPK13, is essential for ethylene-induced aerenchyma formation in rice roots under oxygen-deficient conditions.